Faktor-faktor yang berhubungan dengan pengetahuan penata anestesi tentang resusitasi jantung paru (rjp) pada era pandemi covid-19: Factors associated with nurses anesthetists’ knowledge of cardiopulmonary resuscitation (cpr) in the covid-19 pandemy era - Ni Made Dewi Wahyunadi; Devi, NLP Lusiana; Sudiana, I Ketut (Bali Medika Jurnal, 2021)
This study was conducted to assess the factors (age, gender, education, workplace, working experience and training) associated with the nurses anesthetists’ knowledge of Cardiac Pulmonary Resuscitation (CPR) in the COVID-19 pandemic era. This descriptive correlation study used a cross-sectional approach involved 109 nurses anesthetist as a sample. This study employed total sampling technique. The questionnaire used was adapted from the American Heart Association (2020). Based on the Chi square test, There was a significant relationship between  age (p value = 0,044) and working experience (year) (p value = 0.024) with the nurses anesthetists’ knowledge of CPR in the COVID-19 pandemic era. Otherwise There was no significant relationship between gender (p value = 0,613), education (p value = 0,350), workplace (p value = 0,408), and training (p value = 0,632) with the nurses anesthetists’ knowledge of CPR in the COVID-19 pandemic era. The factors that significantly related to the nurses anesthetists’ knowledge of CPR in the COVID-19 pandemic era are age and working experience. The factors which unrelated are gender, education, income, workplace, and training.